Production of Cellulose by Gluconacetobacter sp. - M. K. Mishra1; A.V. Manwar2, S.U. Pokalwar1* (Recent Research in Science and Technology, 2010)
Abstract Bacterial cellulose (BC) displays unique physical, chemical and mechanical properties including high crystallinity, high water holding capacity, large surface area, elasticity, mechanical strength and biocompatibility. It has found to be very beneficial in the treatment of second and third degree burn cases. BC appears to be one of the best materials to promote wound healing from burns. Another important aspect of BC is preservation of natural resources (plants).Â The use of trees for the production of paper and construction materials leads to deforestation. Bacterial Cellulose seems to be the only alternative for plant cellulose because bacterial cellulose has better physicochemical properties. Also the production rate of bacterial cellulose is faster than plant cellulose production. Keywords: Biopolymer, Bacterial cellulose, Biocompatibility, Physicochemical properties